Coordinated Implementation of Climate-Smart Practices in Coffee Farming Increases Benefits at Farm, Landscape and Global Scale - Schmidt, Paul Günter; Bunn, Christian (Frontiers in Climate, 2021)
Coffee is a major commodity crop that shapes large shares of tropical landscapes. However, the sustainability of these landscapes is threatened by climate change. Whilst adopting climate-smart (CS) practices clearly offers direct benefits to local farmers, their greater benefits accruing at landscape and global scales has not been studied for specific commodity crops so far. Our research uniquely outlines how local adoption of CS-practices in coffee-farming systems provides local, landscape and global benefits. We review literature on CS agriculture, CS landscapes, and coffee farming to firstly identify the different CS-practices applicable to coffee farming systems, and then group these into functional groups that represent the main functional trait targeted by different practices within coffee-farming systems. This allows identifying benefits provided at local, landscape and global scales. The seven functional groups identified are: soil characteristics; water management; crop and genetic diversity; climate buffer and adjustment; crop nutrient management; structural elements and natural habitats; and system functioning. Benefits offered at landscape and global scales (non-exhaustively) include improved water quality, biodiversity conservation and habitat connectivity, as well as stabilized regional climate patterns. Our review shows that regulating services are especially pronounced, although the extent of benefits provided depend on landscape coordination. We discuss considerations for managing possible conflicts, coordinating actions, financing and accommodating lead time. Local farmers, policy-makers and global donors must unite to improve uptake of CS coffee-production practices in a coordinated way, to thereby augment and safeguard coffee-farming’s socio-ecological system along with associated local, landscape, and global benefits.